Penerapan Strategi Digital Marketing dalam Meningkatkan Traffic Penjualan Ritel (Studi Kasus Pada Brand Ritel Sakinah Mart) - Intan Wiani; Riya Datuljannah Dita; Nanda Akhilla Zahra; Syakirotul Hayati; Rusdi Hidayat N; Lidya Veronica Christy Rihidima (CV. Lenggogeni Data Publishing, 2026)
This study aims to analyze the implementation of digital marketing strategies for Sakinah Mart, a Sharia-based retail business operating in Surabaya, Indonesia. Using a Systematic Literature Review (SLR) approach, this research synthesizes findings from national journal articles published between 2021 and 2025 that discuss digital marketing in the retail sector, consumer behavior, website traffic, and sales performance. The analysis identifies six digital marketing strategies relevant to Sakinah Mart, including social media utilization, SEO optimization, content marketing, digital analytics, Sharia-based brand strengthening, and digital promotion enhancement. The study also reveals supporting and inhibiting factors influencing digital marketing effectiveness. Supporting factors include an understanding of the target market, appropriate platform selection, digital infrastructure readiness, skilled human resources, relevant content management, and the ability to use digital analytics. Conversely, Sakinah Mart faces challenges such as limited digital human resources, restricted promotional budgets, and rapidly changing algorithms and content trends. Competitor analysis indicates that Sakinah Mart can remain competitive by strengthening community-based digital content, offering creative promotions, collaborating with MSMEs and local communities, and developing unique loyalty programs. The findings highlight that digital marketing is essential for increasing brand awareness, customer engagement, store traffic, and online-to-offline conversion, particularly for Sharia-based retail businesses in a highly competitive market.